Brain mitochondrial injury induced by oxidative stress-related events is prevented by tamoxifen - Moreira, Paula I. (2005)
This study evaluated the effect of the synthetic, nonsteroidal antiestrogen drug tamoxifen on the function of brain mitochondria. We observed that tamoxifen concentrations above 30 nmol/mg protein induced a slight decrease on RCR and ADP/O ratio. However, only higher concentrations of tamoxifen (>=70 nmol/mg protein) affected the phosphorylative capacity of mitochondria. Those effects were characterized by a decrease on mitochondrial transmembrane potential ([Delta][Psi]m) and repolarization level and an increase on repolarization lag phase with a decrease in ATP levels. Moreover, our results also show that tamoxifen presented a potent capacity to inhibit hydrogen peroxide formation and reduced the extent of lipid peroxidation induced by the pro-oxidant pair ADP/Fe2+. Tamoxifen also exerted some protection against mitochondrial permeability transition pore (MPT) opening, although in a smaller extension than that promoted by cyclosporin A, the specific inhibitor of the MPT. However, in the presence of tamoxifen plus cyclosporin A, the protection observed was significantly higher when compared with that induced by both agents alone. Furthermore, tamoxifen avoided the oxidation of thiol groups and GSH depletion promoted by Ca2+.